Crises and Conflicts on the Way to Sustainable Tourism Development: A Study of Cox’s Bazar, Bangladesh - BHUIYAN, Mohammad Rakib Uddin; BHUIYAN, M. Badruzzaman (Journal of Environmental Management and Tourism, 2023)
This study aims to measure the sustainable tourism conditions of Cox's Bazar, Bangladesh, concerning various crises and conflicts inflicted upon it in recent times. Recent crisis studies make it imperative that sustainability should set the bedrock of any industry for its longevity. Following Ko's (2005) tourism sustainability conceptual framework, this study uses a mixed-method approach to map the tourism sustainability of Cox's Bazar. Our studies find that the tourism sustainability in Cox's Bazar hit an intermediate level in the tourism sustainability map suggested by Ko (2005), which depicts that tourism sustainability in Cox's Bazar is neither sustainable nor unsustainable. Lack of reliable crisis response mechanism, lethargic attitudes towards safety and security issues, no control over the market and city development, relaxed attitudes towards the environment and littering in the tourist zones, and Rohingya people's engagement with drug, human trafficking, and flesh trade can be the most significant challenges to the long-term tourism sustainability of Cox's Bazar. However, a time-suited coordinated tourism action plan can put the tourism sustainability of Cox's Bazar back on the pedestal.